IMPACT OF DEMONETIZATION ON INDIAN ECONOMY - Amit Ratilal Popat (Vidhyayana - An International Multidisciplinary Peer-Reviewed E-Journal - ISSN 2454-8596, 2020)
Demonetization is a process by which a series of currency will not be legal tender. The 8 November 2016 was a shocking day for the population of India when the government announced that the Rs.500 and Rs.1000 notes will not be a legal tender. The aim of the demonetization is to eradicate black money, putting an end to fake currency circulation, stop funding terrorism, transparency in dealings and a move towards cashless economy. It is true that the demonetization has paved way for digital banking trend in India. This research paper aims at giving an overview of demonetization impact on Indian economy & its sector it also gives an idea about the cashless economy which may change by the introduction of demonetization.